FORMUŁY SUBSKRYPCYJNE STOSOWANE W DOKUMENTACH ARCYBISKUPA JAROSŁAWA BOGORII SKOTNICKIEGO ORAZ PERSONEL KANCELARII ARCYBISKUPIEJ W LATACH 1345-1374 - Alina Polak (In Gremium. Studies in History, Culture and Politics, 2012)
SUBSCRIPTION FORMULAS USED IN ARCHBISHOP JAROSŁAW BOGORIA SKOTNICKI'S DOCUMENTS AND BY THE STAFF OF THE ARCHBISHOP'S OFFICE IN YEARS 1354-1374The workers at archbishop Jarosław Bogoria Skotnicki's office (pontificate from 1342 to 1374) needed suitable education not only to rewrite ready templates but also to edit documents on their own. The staff of the metropolitan office included such clerks as chancellors, vice-chancellors, notaries, pro-notaries, and writers. It has been confirmed that there were 15 such employees in the times of this metropolitan bishop. The duties of an archbishop's chancellor included editing and writing documents and looking after the archbishop's and chapter's seal.The notaries edited and sometimes wrote documents and the scriptors only wrote documents. The scripting formulas known in the office in Gniezno were scriptum per manus, datum per manus and transivit per manus. The two last ones were probably used alternatively according to the individual preferences of a particular datary who was most likely responsible for the entire course of creating a diploma and the legality of its content.